Locally produced natural conditioners for dewatering of faecal sludge. Issue 21 (1st November 2016) - Gold, Moritz; Dayer, Pauline; Faye, Marie Christine Amie Sene; Clair, Guillaume; Seck, Alsane; Niang, Seydou; Morgenroth, Eberhard; Strande, Linda
ABSTRACT: In urban areas of low-income countries, treatment of faecal sludge (FS) is insufficient or non-existent. This results in large amounts of FS being dumped into the environment. Existing treatment technologies for FS, such as settling-thickening tanks and drying beds, are land intensive which is limiting in urban areas. Enhanced settling and dewatering by conditioning was evaluated in order to reduce the treatment footprint (or increase treatment capacity). Conventional wastewater conditioners, such as commercially available lime and polymers, are expensive, and commonly rely on complex supply chains for use in low-income countries. Therefore, the treatment performance of five conditioners which could be produced locally was evaluated: Moringa oleifera seeds and press cake, Jatropha curcas seeds, Jatropha Calotropis leaves and chitosan. M. oleifera seeds and press cake, and chitosan improved settling and dewatering and had a similar performance compared to lime and polymers. Optimal dosages were 400–500 kg M. oleifera /t TS, 300–800 kg lime/t TS and 25–50 kg polymer solution/t TS. In comparison, chitosan required 1.5–3.75 kg/t TS. These dosages are comparable to those recommended for wastewater (sludge). The results indicate that conditioning of FS can reduce total suspended solids (TSS) in the effluent of settling-thickening tanks by 22–81% and reduce dewatering time with drying beds by 59–97%. This means that the area of drying beds could be reduced by 59–97% with end-use as soil conditioner, or 9–26% as solid fuel. Least expensive options and availability will depend on the local context. In Dakar, Senegal, chitosan produced from shrimp waste appears to be most promising.